Progress Report on Gender Data Collection - Nchanji, Eileen Bogweh; Muteti, Thomas (CGIAR Initiative on Gender Equality, 2022)
The Bundles Innovations for Women’s Empowerment work package (WP 2), co- led by the Alliance of Bioversity and CIAT (ABC), is meant to design and collect systematic evidence on whether and how STIBs (Socio-Technical Innovative Bundles) can enhance women’s empowerment and resilience to later design and implement context-specific and gender-responsive STIBs. We intend to build on available and relevant CGIAR and non-CGIAR innovations through learning labs to enhance their uptake and impacts via enhancing women’s access, resilience, and empowerment. The overall objective of the consultancy is to contribute by identifying and pulling out information on existing socio-technical from different data sets across the CGIAR and visualize it in various formats; however, for this report, we have only started with the CGIAR Gender impact platform, which houses most of the gender datasets.